Serum Lactate Level Predicts Short-Term and Long-Term Mortality of HBV-ACLF Patients: A Prospective Study - Nie Y; Zhang Y; Liu L; Zhu X (Dove Medical Press, 2020)
Yuan Nie,* Yue Zhang,* Lin-xiang Liu, Xuan Zhu Department of Gastroenterology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuan ZhuDepartment of Gastroenterology, The First Affiliated Hospital of Nanchang University, No. 17, Yongwaizhengjie Road, Donghu District, Nanchang 330006, Jiangxi, People’s Republic of ChinaEmail jyyfyzx@163.comBackground: Acute chronic liver failure (ACLF) is a high-mortality disease characterized by rapid deterioration of liver function and multiple organ failure. The aim of this study was to assess the short-term and long-term predictive values of serum lactate in HBV-ACLF patients to facilitate early treatment and thereby improve patient survival.Methods: We conducted a single-center, observational prospective study of 108 hospitalized patients. Biochemical examination and demographic data were obtained within 24 hours of admission. Logistics analysis was used to determine whether serum levels were independently for prognosis of HBV-ACLF patients. The area under ROC curve evaluates the prediction accuracy compared to the existing score.Results: Serum lactate levels in nonsurviving patients were significantly higher than those in surviving patients. Logistics analysis demonstrated that serum lactate was an independent risk factor for 28-day, 3-month, and 6-month mortality. ROC curve evaluates the prediction efficiencies of serum lactate for 28-day, 3-month, and 6-month mortality. The AUROCs of new scores by adding lactate (Child-Pugh+ lactate score, MELD+ lactate score, MELD-Na+ lactate score, CLIF-C OF+ lactate score, CLIF-SOFA+ lactate score, CLIF-C ACLF+ lactate score) were superior to those of existing scores, particularly the MELD score and MELD-Na score (P< 0.05) at all time points.Conclusion: Serum lactate can be used as an effective indicator to predict the short-term and long-term mortality in HBV-ACLF patients, and the predictive value of the MELD score and MELD-Na was improved by adjusting for lactate. Lactate testing at admission can be beneficial in prognostic assessment and clinical decision-making.Keywords: acute-on-chronic liver failure, HBV, prognosis, lactate, scoring model